PREDICTIVE ROLE Of SUPPLIER INNOVATION MANAGEMENT in the PERFORMANCE of MICRO, SMALL and MEDIUM HOTELS in NAIROBI - Munene, Doctor Mary Mwihaki; Mukulu, Professor E. (IJRDO - Journal of Applied Management Science, 2017)
Businesses continue being highly complex due to various reasons such as competition, growthin size, an educated workforce, change in technology amidst other factors, the predictive roleof supplier innovation management cannot be denied. This study looks at the various factorsthat entrepreneurs should concentrate on to achieve success in supplier innovationmanagement. These include supplier relations, supplier involvement and capability, automatedsystems, and supplier data analysis. Literature was reviewed from various sources ofsecondary data with the aim of finding out what various scholars have to say about thecontribution of supplier innovation management to firm performance. Data was collected byIJRDO-Journal of Applied Management Science ISSN: 2455-9229 Volume-3 | Issue-11 | November,2017 | Paper-4 49 use of exploratory design, through personal interviews on 100 sampled hotels. The data wasprocessed using correlation and multiple regression analysis. The results showed that supplierinnovation management had no significant predictive role in the performance of micro, smalland medium hotels. The negative results may have need as a result of poor implementation bythe Nairobi hotels and travel advisories by various tourist destinations. To be successful insupplier innovation management it was important for hotels to generate proper supplierrelationships, be highly professional and ethical and transparent among other factors.